RETORSJA POKRZYWDZONEGO PRZY PRZESTĘPSTWACH PRZECIWKO CZCI I NIETYKALNOŚCI CIELESNEJ A ZASADA ‘DE SUA MALITIA NEMO DEBET COMMODUM REPORTARE’ - Drewicz, Marcin (Zeszyty Prawnicze, 2016)
The Victim’s Retaliatory Response to Offences Against His Honour And Physical Integrity and the Principle of ‘de sua malitia nemo debet commodum reportare’ Summary The aim of this paper is to discuss a victim’s retaliatory action against the perpetrator of an offence against his honour and physical integrity as a circumstance admitting the waiving of penalisation. The possibility for the offender to evade penalisation simply because the victim retaliated seems to contradict the principle that the offender should draw no benefit from the offence (de sua malitia nemo debet commodum reportare). The regulation adopted in the Polish Criminal Code (kodeks karny, k.k.) appears to favour the offender who received a retaliatory response from the victim, over and above the situation in which the victim took no measures to retaliate against the offender. The article also highlights the difference in the legal consequences of the waiving of penalties respectively for the perpetrator and the retaliating victim. This differentiation, which puts the retaliating victim in a worse position than the offender, also appears to be incompatible with the cited principle of criminalisation.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />